A dual speech encryption algorithm based on improved Henon mapping and hyperchaotic - Qiuyu ZHANG; Yujie SONG (Dianxin kexue)
Aiming at the problems of small key space, poor security, low encryption efficiency, and the inability to realize the trade-off between key complexity and encryption efficiency of existing speech chaotic encryption algorithms, a dual speech encryption algorithm based on improved Henon mapping and hyperchaotic was proposed.Firstly, the traditional Henon mapping was improved by extending the control parameter range and taking the nonlinear trigonometric function as the input parameter variable, which made the Henon mapping have larger chaotic space and higher chaotic complexity.Secondly, the improved Henon mapping was used to generate pseudorandom sequence, and the speech data was encrypted single time without repeated scrambling to obtain the first time encryption results of the speech data.Finally, Lorenz hyperchaotic system was adopted to encrypt the speech data after the first time encryption by Arnold secondary scrambling encryption and XOR diffusion encryption to obtaining the final ciphertext speech data.The experimental results show that, compared with the existing methods, the proposed algorithm have larger key space, higher encryption efficiency, and stronger robustness against various cryptographic attacks.